2016
DOI: 10.1016/j.colsurfa.2016.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic comparative study of foam flow between a classical and a pH sensitive surfactant

Abstract: International audienceComparative study between foams made of a pH sensitive surfactant, nonaoxyethylene oleylether carboxylic acid (AKYPO® RO 90 VG) and a classical foaming surfactant, sodium dodecyl sulphate (SDS) was realised using simple microfluidic devices in the scope of Enhanced Oil Recovery (EOR). The influence of injecting fluid parameters such as gas and foaming liquid pressure was investigated and discussed in terms of foam morphology, and lamellae stability and curvature radii. The increasing stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…They reported that a foam generation operation could be controllable by varying the applied pressure. A similar study using a microfluidic device was carried out to understand the mechanism for foam generation and suggested that the pressure of the injection fluid is the primary mechanism for foam generation . A recent microfluidic study reported that during the brine flooding (secondary) method, oil trapped in the high-permeability zone was recovered as well as a small fraction from the low-permeability zone.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…They reported that a foam generation operation could be controllable by varying the applied pressure. A similar study using a microfluidic device was carried out to understand the mechanism for foam generation and suggested that the pressure of the injection fluid is the primary mechanism for foam generation . A recent microfluidic study reported that during the brine flooding (secondary) method, oil trapped in the high-permeability zone was recovered as well as a small fraction from the low-permeability zone.…”
Section: Introductionmentioning
confidence: 96%
“…A similar study using a microfluidic device was carried out to understand the mechanism for foam generation and suggested that the pressure of the injection fluid is the primary mechanism for foam generation. 30 A recent microfluidic study reported that during the brine flooding (secondary) method, oil trapped in the high-permeability zone was recovered as well as a small fraction from the lowpermeability zone. This result showed that the sweep efficiency of the microfluidic device is lower and suitable for chemical flooding.…”
Section: Introductionmentioning
confidence: 99%
“…As the formation of low quality foams, witnessed for f g ≥ f g * , is very detrimental for industrial applications, a key issue is therefore to rationalize this phenomenon. Such a task is in fact necessary to screen the formulation of the surfactant solutions that are to be coinjected , and thus looking for increasing f g * while optimizing foam viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…At the bubble scale, it allows one to directly observe the dynamic of gas snap-off or bubble–bubble pinch-off mechanisms. At the foam scale, it can be used for instance to visualize the flow of foam in micromodels with different permeabilities, , study the hysteretic behavior of foam or the dislocation dynamics in a two-dimensional crystal foam flowing in a tapered channel, control the foamability of surfactants, or investigate the destabilization, propagation, and generation of foam during the movement of crude oil in heterogeneous model porous media . The geometry of the single pore used in our study is similar to that of a planar flow focusing device .…”
Section: Introductionmentioning
confidence: 99%
“…When the foam is generated, an important increase of the pressure gradient is observed, resulting from the increase of effective gas viscosity and a IFP Energies nouvelles, 1 et 4 avenue de Bois-Préau, 92852 Rueil-Malmaison, France * E-mail: raphael.poryles@yahoo.fr and loic.barre@ifpen.fr the decrease of relative permeability leading to a reduced mobility factor 8,11,12 . Many studies have been performed in quasi 2D Hele-Shaw cells and micromodels to observe the dynamics of the foam flow at the bubble scale [13][14][15][16][17][18][19][20] . Those experiments have shown many results including that bubbles can be trapped inside a single pore and that fragmentation and coalescence processes can occur.…”
Section: Introductionmentioning
confidence: 99%